Synthesis, formation and characterization of lead zirconate titanate-lead zinc niobate powders - Penphitcha Amonpattaratkit (2018)
xPb(Zr1/ 2 Ti1/ 2 )O 3 -(1-x)Pb(Zn1/ 3 Nb2/ 3 )O 3 or xPZT-(1-x)PZN (x = 0.85-0.95)powders were prepared by a modified mixed-oxide synthetic route via a combination of Zn 2 Nb 34 O 87 precursor and rapid vibro-milling techniques. Effects of calcination temperature on phase formation, morphology, particle size and chemical composition of perovskite ferroelectric powders in the solid solution of PZT-PZN system were investigated. Perovskite phase transition from a tetragonal to a coexistence of tetragonal and rhombohedral phases occurred as composition and firing temperature change. The tetragonality factor and degree of spherical grain shape were observed to increase with increasing PZT content. Moreover, the degree of agglomeration and averaged particle size of the PZT-PZN powders were also found to increase at higher calcination temperatures. © 2013 Copyright Taylor and Francis Group, LLC.